Synthesis, Characterization and Biological Studies of Cu(II), Ni(II), Co(II) Complexes Containing Mixed Ligand - Singh, Vijendra; Singh, Dharmendra; Kumar, Rakesh; Lata, Suman; Sharma, Munesh (Asian Journal of Chemistry, 2010)
The mixed ligand metal complexes were prepared by using 4,7-dimethyl-1,10-phenanthroline (phen.), 2-hydroxybenzalidine anthranilic acid (HBAA) and M(CH3COO)2 [M = Cu(II), Ni(II), Co(II). The prepared mixed ligand metal complexes have been characterized on the basis of elemental analysis, infrared spectra, electronic spectra, magnetic susceptibilities and molar conductivity measurements. The microbial activities of mixed ligand metal complexes were tested against Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger, Escherichia coli and Staphylococcus aureus.